Arte y sociedad en plena transformación hacia el siglo xxi. el arte japonés contemporáneo (1998)
At the celebration of the fiftieth anniversary of A.l.C.A. (InternationalAssociation of Art Critics, an organization sponsored by UNESCO), held inTokyo recently, the XXXII World Congress of Art Critics provided aspecial occasion to offer an in-depth analysis of creative expression in art,particularly in regard to the relationship between tradition and globalization.With the attendance of more than a hundred critics and specialists fromOceanía and various Asían, European, North and Latin American countries,an interesting debate ensued and opportunities arose that furthered thediscussion of similar problems and concerns in an Asiatic country whoseprivileged position at the coming of the next century is more than evident.